Análise crítica de incubadoras neonatais a partir de medições de parâmetros dos ambientes interno e externo - Costa, Enilson José Lima (2009)
The survival chances of premature newborns increases when the air temperature and relative humidity of the incubator environment are under control. Newborn incubator is an electromedical equipment used for life maintenance of premature newborns. It provides a thermo-neutral environment, achieved by keeping the air temperature and relative humidity within a suitable range. This allows the baby to maintain the normal body temperature without excessive metabolic losses and contributes to a faster development and a smaller incidence of diseases. In this thesis, a measurement system capable to assess newborn incubators by measuring the internal and external environment parameters was designed and development. Also, it was developed a system to control the relative humidity of the incubator environment. In additional, a data acquisition software was developed to manager measured parameters inside the newborn incubator such as: air temperature, relative humidity, sound level and air flow velocity. Thus, it is possible to check if an incubator, under analysis, meets the requirements established by the NBR IEC 601-2-19 standard. Experimental tests were carried out in a time period of 96 hours and the measured data were collected at each 2 minutes. The results showed that all newborn incubators, which were assessed by the developed system, do not provide adequate environment for premature newborns as these incubators do not meet the NBR IEC 601-2-19 standard requirements.